2003
DOI: 10.3748/wjg.v9.i12.2843
|View full text |Cite
|
Sign up to set email alerts
|

Plasma matrix metalloproteinase-1 and tissue inhibitor of metalloproteinases-1 as biomarkers of ulcerative colitis activity

Abstract: AIM:Overexpression of mucosal metalloproteinases (MMP) have been demonstrated recently in inflammatory bowel disease. Their activity can be counterbalanced by the tissue inhibitor of metalloproteinases (TIMP). The aim of this study was to evaluate the effect of ulcerative colitis (UC) on MMP-1 and TIMP-1 plasma concentrations, as two possible biomarkers of the disease activity. METHODS:MMP-1 and TIMP-1 plasma concentrations were measured with an enzyme immunoassay in 16 patients with endoscopically confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…In inflammatory bowel disease tissue, both mRNA transcripts and protein levels of this inhibitor were increased [13,19]. Raised levels of soluble TIMP-1 have been found in culture supernatants of inflamed biopsies from ulcerative colitis and Crohn`s disease patients [32,33]. Increased soluble TIMP-1 levels were found in synovial fluid [27] and serum samples of rheumatoid arthritis patients [28].…”
Section: Discussionmentioning
confidence: 93%
“…In inflammatory bowel disease tissue, both mRNA transcripts and protein levels of this inhibitor were increased [13,19]. Raised levels of soluble TIMP-1 have been found in culture supernatants of inflamed biopsies from ulcerative colitis and Crohn`s disease patients [32,33]. Increased soluble TIMP-1 levels were found in synovial fluid [27] and serum samples of rheumatoid arthritis patients [28].…”
Section: Discussionmentioning
confidence: 93%
“…In experimental colitis, MIF expression was increased during colitis and the severity of colitis was reduced by anti-MIF antibody [68], which suppressed T-helper 1-type cytokines and matrix metalloproteinase (MMP). It has been reported that MMP is overexpressed in infl ammatory bowel disease (IBD) and in experimental colitis [69]. Moreover, MIF-defi cient mice showed mild infl ammation compared with wild-type mice [70].…”
Section: Mif and Infl Ammatory Diseasesmentioning
confidence: 99%
“…116,117 TIMP-1 levels also inversely correlated with scored endoscopic degree of mucosal injury, disease activity index, and clinical activity index values in patients with UC. 118 In IBD, TIMP-3 is expressed around blood vessels, within the macrophage-rich area, below the neutrophilic infiltrate of the ulcer bed, and in the lamina propria surrounding damaged crypts. 16 The ratio between MMP-1/TIMP-1 and MMP-3/TIMP-1 is increased in inflamed colon of IBD patients compared with noninflamed tissue samples, whereas TIMP-2 mRNA remained unaltered.…”
Section: Tissue Inhibitors Of Mmp (Timp)mentioning
confidence: 99%